FAKTOR-FAKTOR PENYEBAB RAMPAN KARIES PADA SISWA TK BUDI UTAMI DI DAERAH PESISIR PANTAI DESA BERAHAN WETAN KECAMATAN WEDUNG KABUPATEN DEMAK - Bambang Sutomo; Tiara Uyun Hanifah; Salikun Salikun; Suryo Ediyono (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2018)
TITLETHE FACTOR OF CAUSING RAMPANT CARIES IN THE KINDERGARTEN STUDENTS IN THE COASTAL AREAS WEDUNG, DEMAKABSTRACTBaby bottle caries is a dental disease that attacks the hard tissues of tooth that spreads rapidly and it’s common in primary teeth. This study aims to determine the factors that cause baby bottle caries in Budi Utami Kindergarten students in coastal areas of Berahan Wetan Village Wedung District Demak Regency 2016.This type of research is quantitative descriptive case study method. Data taken by direct examination of the baby bottle caries, the pH of saliva and plaque index PHP-M, as well as the provision of a questionnaire and a questionnaire based on the theory of H.L. Bloom approach which consist by environmental factors, behavior, health care and heredity. Priority issues using odd ratiotest data analysis showed that the practical factor (OR value=16,25), attitude factor (OR value=15,00) and knowledge factor (OR value=9,3) are the most dominant causative factors to the baby bottle caries problem.The results showed that the salivary pH value all of respondents were in acid criteria (pH 7.0) and 57% respondents have a bad plaque index score categories. The time factor showed 57% of respondents are in the bad category. Knowledge factors, there are still 48% of respondents who are knowledgeable with the bad category. Attitude factors, as much as 61% of respondents already have a good attitude. Practices factors, 100% of respondents do not brush the teeth before going to bed at night and do not check their teeth regularly. Environmental factors, found 83% of respondents have the habit of toothbrushing only when having take a bath. Health services factors, 100% of respondents had never obtained the treatment of cavities and did not get dental health education. Heredity, found 52% of respondents have a fragile teeth and 26% of respondents have a crowding tooth structure. The alternative solutions to problems are by minimize baby bottle consumtion, cariogenic food dietary, brushing teeth together at school, topical application of fluoride or CPP-ACP, dental health education for students and school cadres training.